ANALYSIS OF THE IMPACT OF THE JOINT LIABILITY FINANCING SYSTEM ON PNM MEKAAR CUSTOMERS IN MEDAN CITY FROM AN ISLAMIC ECONOMIC PERSPECTIVE - Ismail, Abdurrozzaq; Saparuddin Siregar; Bi Rahmani, Nur Ahmadi (International Journal of Cultural and Social Science, 2025)
PT. Permodalan Nasional Madani (PNM) continues to strengthen the people's economy by empowering MSME customers fostered by PNM Mekaar. Financing provided by PNM Mekaar is distributed in groups from the beginning, agreed upon by each member. This research was conducted at Medan City. This research was conducted to determine and analyze the implementation of the joint liability financing system on customers, the socio-economic impacts experienced by customers related to the implementation of the joint liability financing system, as well as the perspective of Islamic economics on the impact of the joint liability financing system on PNM Mekaar Medan City customers. The approach in this research applies descriptive qualitative research using primary and secondary data. Data collection techniques through observation, interviews and documentation with data analysis using the Miles and Huberman model. The results of the study show that: 1). The implementation of the joint liability financing system on PNM Mekaar Medan City customers shows that this mechanism does not only function as a financial instrument, but also as a means of strengthening solidarity, togetherness and collective responsibility among group members. 2). The socio-economic impacts experienced by customers related to the implementation of the PNM Mekaar Medan City joint financing system show the benefits and challenges directly felt by group members. This system has been proven to encourage increased business capital, increased income and improved family economic conditions through the sustainability of more stable micro-business activities. In addition, the group-based mechanism is able to strengthen solidarity, togetherness, discipline and collective responsibility among members, as well as open up opportunities for business independence that were previously difficult to achieve. 3). The Islamic economic perspective on the impact of the joint financing system on PNM Mekaar Medan City customers can be seen as aligned with Islamic principles because it emphasizes the values of justice, togetherness, transparency of contracts, prohibition of usury, freedom from coercion and the application of the principle of ta'?wun (mutual assistance).